Evaluation of Sustainability Practices in Higher Education using ESG Concepts - Tjahjono, Gabriella Agnes Kurnia (Indonesian Journal of Sustainability Accounting and Management, 2025)
This research aimed to evaluate sustainability practices carried out by internal stakeholders using the ESG concept. In addition, it also identified opportunities and challenges faced when carrying out sustainability practices which were then given suggestions for improvement. This research used a case study approach to evaluate the overall situation in the field. The author conducted 14 semi-structured interviews with deans, teaching staff, and students who have been involved in the process of sustainability practices at the business school. Analysis revealed that sustainability was embedded in narratives at different levels of practice. The respondents revealed how they could respond to sustainability based on their emotions and understanding and the direct of ESG practices. As business schools as part of higher education contributed to achieving SDGs, some practices were still unfulfilled due to several factors. Various considerations and plans needed to be improved, especially on awareness and policy attitudes. This study referred to Schatzki’s framing of practice theory used to reveal the extent to which the level of practice was based on an operational overview through various perspectives and activities when carrying out processes using ESG concepts by considering the emotional and understanding components of carrying out sustainability practices.